Navigating Sequencing in Relapsed/Refractory Multiple Myeloma: Canadian Experts Discuss the Evidence and the Evolving Options (Canadian Hematology Today, 2026)
Relapsed and refractory (R/R) multiple myeloma presents increasingly complex therapeutic decisions. Clinicians must not only weigh efficacy and tolerability but consider how today’s treatment decisions will affect future options. In a roundtable discussion, myeloma experts discuss practical approaches to sequencing therapies across diverse patient scenarios.